Making sense to decreasing citizen eParticipation through a social representation lens. Issue 3 (September 2016) - Pozzebon, Marlei; Cunha, Maria Alexandra; Coelho, Taiane R.
Abstract: This paper investigates the development of an electronic platform by a local government with the goal of increasing citizens' participation in public decision-making process, particularly the modality known as participatory budgeting. The local government of Belo Horizonte, a Brazilian municipality, decided to use web-based technologies to create a project called digital participatory budgeting (DPB), whose purpose was to include new segments of the population –particularly the middle class and youth – in the process of prioritizing the allocation of investments in the city's public works. The project was launched in 2006 and repeated in 2008 and 2011. Intriguingly, however, citizen participation decreased significantly. This study seeks to understand why citizens' participation decreased over time, despite the availability of a cutting-edge, user-friendly and iterative web-based platform to help connect citizens to the process. The theoretical approach is based on social representation theory (SRT) and the methodology of critical discourse analysis (CDA) of 101 documents and 19 interviews. This combination of SRT and CDA helps in understanding how people gave meaning to a new social object - the digital participatory budgeting – through their voices. Simultaneously, this approach represents a skillful approach to uncovering power imbalances signaled by "silences". The results suggest that deviations in the social representation process, namely, trivialization and reification, help us to understand the process through which citizen participation decreases. Therefore, governments seeking to improve eParticipation should, without neglecting the technical aspects, pay more attention to the social representational processes that characterize their web-based initiatives. Highlights: We investigate the role of social representations in processes of public decision-making participation. The theoretical approach is based on social representations theory. The methodology is based on critical discourse analysis. Trivialization and reification in the social representation process helps to explain why participation decreases. Our results emphasise the explanatory role of discursive practices.